Extreme and exposed symmetric bilinear forms on the space ${\mathcal L}_{s}(^2 l_{∞}^2)$ - Sung Guen Kim (Karpatsʹkì Matematičnì Publìkacìï, 2020)
We classify extreme points and exposed points of the unit ball of the space of bilinear symmetric forms on the real Banach space of bilinear symmetric forms on $l_{∞}^2.$ It is shown that for this case, the set of extreme points is equal to the set of exposed points.